2012
DOI: 10.1002/jgm.2609
|View full text |Cite
|
Sign up to set email alerts
|

Truncated peptides from melittin and its analog with high lytic activity at endosomal pH enhance branched polyethylenimine‐mediated gene transfection

Abstract: The results obtained in the present study indicate that the truncated peptides with higher endosomal disrupting activity were better enhancers for increasing transfection efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…We will also further improve these materials by incorporating different melittin analogs that were reported to mediate efficient transfection without compromised cell viability. [30, 32, 37, 46, 47]…”
Section: Discussionmentioning
confidence: 99%
“…We will also further improve these materials by incorporating different melittin analogs that were reported to mediate efficient transfection without compromised cell viability. [30, 32, 37, 46, 47]…”
Section: Discussionmentioning
confidence: 99%
“…This could pose difficulties given melittin's initial electrostatic attraction to negatively charged lipid components. In fact, detailed biophysical studies have revealed that melittin's ability to bind to and disrupt model membranes actually decreases as pH decreases (Tan et al 2012). Nonetheless, melittin has been shown to be capable of altering endosomal membrane integrity after cellular uptake under sub-toxic concentrations, suggesting that melittin does bind to and alter endosomal membranes despite the acidic environment (Rozema et al 2003).…”
Section: Melittin As a Basis For Endosomal Escapementioning
confidence: 99%
“…As we show below, endosomal release can be very inefficient (19,25,29,30) and can effectively prevent the delivery of some endocytosed cargos to the cytosol. Given this roadblock to delivery, various approaches based on physical or osmotic lysis of endosomes have been tested to increase the efficiency of endosomal release postuptake (22,29,(31)(32)(33)(34). Still, despite significant efforts over the last two decades, the highly cationic cell-penetrating peptides have yet to achieve their potential as delivery vehicles in the laboratory or in the clinic.…”
mentioning
confidence: 99%